Aeromonas Salmonicida Infection in A Massive Splenic Cyst: A Rare Cause of an Acute Abdomen - Akram, Norfaidhi; MNA, Abdul Rahman; O , Faidzal (IIUM Medical Journal Malaysia, 2020)
Introduction: Cysts of the spleen are most frequently primary or secondary. If it contained an epithelial lining it is referred to as epithelial or epidermoid cysts Other common cause is post-traumatic pseudocysts. Non parasitic cause of infective splenic cyst are rare especially those caused by bacterial infection. They may present as symptoms related to their size with gastric compression or pain, an abdominal mass, rupture, or infection with abscess. Case report: We present a case of massive splenic cyst in a 13 year old boy presenting with acute abdominal pain, this was successfully treated with deroofing of the cyst wall while preserving the function of the spleen. Cultures subsequently grew Aeromonas Salmonicida. The patient was discharged home well. Issues of diagnosis and dilemma in treatment while preserving the spleen in an adolescent will be discussed.